Quality indicators for the primary care of osteoarthritis: a systematic review - Edwards, J J; Khanna, M; Jordan, K P; Jordan, J L; Bedson, J; Dziedzic, K S (Annals of the rheumatic diseases, 2015)
To identify valid and feasible quality indicators for the primary care of osteoarthritis (OA). Systematic review and narrative synthesis. Electronic reference databases (MEDLINE, EMBASE, CINAHL, HMIC, PsychINFO), quality indicator repositories, subject experts. Eligible articles referred to adults with OA, focused on development or implementation of quality indicators, and relevant to UK primary care. An English language restriction was used. The date range for the search was January 2000 to August 2013. The majority of OA management guidance has been published within this time frame. Relevant studies were quality assessed using previous quality indicator methodology. Two reviewers independently extracted data. Articles were assessed through the Outcome Measures in Rheumatology filter; indicators were mapped to management guidance for OA in adults. A narrative synthesis was used to combine the indicators within themes. 10,853 articles were identified from the search; 32 were included in the review. Fifteen indicators were considered valid and feasible for implementation in primary care; these related to assessment non-pharmacological and pharmacological management. Another 10 indicators were considered less feasible, in various aspects of assessment and management. A small number of recommendations had no published corresponding quality indicator, such as use of topical non-steroidal anti-inflammatory drugs. No negative ('do not do') indicators were identified. There are well-developed, feasible indicators of quality of care for OA which could be implemented in primary care. Their use would assist the audit and quality improvement for this common and frequently disabling condition.